2019
DOI: 10.1038/s41598-019-44681-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression analysis of CsCML genes in response to abiotic stresses in the tea plant (Camellia sinensis)

Abstract: Calmodulin-like (CML) proteins are a class of important Ca 2+ sensors in plants, which play vital roles in regulating plant growth and development and response to abiotic stress. Tea plant ( Camellia sinensis L.) is the most popular non-alcoholic economic beverage crop around the world. However, the potential functions of CMLs in either tea plants growth or in the response to environmental stresses are still unclear. In the present study, five CsCML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…With the release of tea reference genome, gene family identification, classification, and function prediction have gradually become new research hotspots Liu et al, 2019;Ma et al, 2019;Wang et al, 2018). With the extreme global climate, low temperature stress and drought stress may adversely affect the growth and development of tea plants and the quality of tea products.…”
Section: Discussionmentioning
confidence: 99%
“…With the release of tea reference genome, gene family identification, classification, and function prediction have gradually become new research hotspots Liu et al, 2019;Ma et al, 2019;Wang et al, 2018). With the extreme global climate, low temperature stress and drought stress may adversely affect the growth and development of tea plants and the quality of tea products.…”
Section: Discussionmentioning
confidence: 99%
“…f. glauca were probably the member of transcription factor families like WRKY, GH3, TIFY/JAZ, CML, ERF, TGA. Coincidently, it has been reported that above transcription factors did be widely involved in various defense responses [58,[90][91][92][93][94][95][96][97][98][99][100][101][102]. It is reported that GH3 and CML can also regulates fruit development [103,104].…”
Section: Resistance Genes (R Genes)mentioning
confidence: 86%
“…f. glauca were probably the member of transcription factor families like WRKY, GH3, TIFY/JAZ, CML, ERF, TGA. Coincidently, it has been reported that above transcription factors did be widely involved in various defense responses [26,[66][67][68][69][70][71][72][73][74][75][76][77][78]. It is reported that GH3 and CML can also regulates fruit development [79,80].…”
Section: Resistance Genes (R Genes)mentioning
confidence: 86%